2017
DOI: 10.1186/s12199-017-0613-z
|View full text |Cite
|
Sign up to set email alerts
|

Description of the healthy eating indices-based diet quality in Turkish adults: a cross-sectional study

Abstract: ObjectivesThis study aims to describe the dietary status of Turkish adults using two different versions of the Healthy Eating Index (HEI).MethodsIn this cross sectional study, 494 healthy participants (311 females) with randomly selected and living in Ankara were included between September 2013 and March 2014. A questionnaire was completed and anthropometric measurements (weight and height) were performed. The 24-h dietary recall of individuals was collected. Diet quality was measured through HEI-2005 and HEI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
5
14
0
Order By: Relevance
“…This finding has been confirmed in other studies [44]. Koksal et al reported that older people had higher total scores in diet quality compared to other age groups [44]. Additionally, this study found gender inequalities regarding diet quality and WC, SBP TG and HDL: our results showed women had better dietary guideline compliance [45] and consequently better metabolic status than men.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding has been confirmed in other studies [44]. Koksal et al reported that older people had higher total scores in diet quality compared to other age groups [44]. Additionally, this study found gender inequalities regarding diet quality and WC, SBP TG and HDL: our results showed women had better dietary guideline compliance [45] and consequently better metabolic status than men.…”
Section: Discussionsupporting
confidence: 90%
“…This inconsistency suggests that age-related reduction of physical activity may be a cause of age-related increases in obesity indices. This finding has been confirmed in other studies [44]. Koksal et al reported that older people had higher total scores in diet quality compared to other age groups [44].…”
Section: Discussionsupporting
confidence: 84%
“…These conclusions may differ according to the population studied given that, in many developed countries, epidemiological studies observed a positive relationship between education and diet quality (34)(35)(36) . Another study that used the HEI-2005 and compared weight, age, sex and educational level of Turkish adults as potential factors for diet quality found that <8 years of education was associated with a diet quality score of 58•3 (SE 13•6) points and the highest education category (>8 years) had a score of 54•7 (SE 14•0) points, coinciding with the present study (49) . In the 2003 ISA-Nutrition (41) , saturated fat and SoFAAS components increased in individuals with a higher education level and an inverse association was found between years of study and BHEI-R.…”
Section: Discussionsupporting
confidence: 87%
“…One possible explanation for this result is that males tend to be less motivated with regards to their eating behavior in comparison to females [ 54 ], even if their spouses promote healthy eating habits at home [ 18 ]. In this sense, previous studies have shown that males have poorer diet quality than females [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 96%